Segmentation pattern and structural complexities in seismogenic extensional settings: The North Matese Fault System (Central Italy). (February 2017) - Ferrarini, Federica; Boncio, Paolo; de Nardis, Rita; Pappone, Gerardo; Cesarano, Massimo; Aucelli, Pietro P.C.; Lavecchia, Giusy
Abstract: We investigated the northern slope of the Matese Mts. (Molise, Central Italy) with the aim of characterizing the N- to NE-dipping active normal fault system in the Bojano basin, a sector of primary importance from a seismic hazard perspective. We collected field data to define the geometry and segmentation pattern of two sub-systems (Patalecchia-Colle di Mezzo and Bojano–Campochiaro). New evidence of late Quaternary faulting was obtained by exploiting well log interpretations. Kinematic analysis revealed the interaction of pre-Quaternary inherited (mainly E-W-striking) and newly formed (NW-SE-striking) normal faults. Slip accommodation through linkage was clearly noted in the case of the Patalecchia-Colle di Mezzo sub-system. Detailed topographic profiles across the active fault segments provided post-LGM (15 ± 3 kyr) slip rates up to ∼2 mm/yr which agree with the high deformation rates based on different approaches in the literature. Finally, the instrumental seismicity analysis constrained the bottom of the seismogenic layer to depths of 13–14 km, and the gathered information allowed us to reconstruct the North Matese seismogenic source. Its 3D geometry and dimensions agree with both the dimension-magnitude relationships and macroseismic information available for the 1805 earthquake (Mw 6.6), the main historical earthquake to have struck the Bojano basin. Highlights: A multidisciplinary approach is used to inspect a segmented active fault system. New field data constrained the fault activation to the Late Quaternary (post LGM). Possible interaction of neo-formed and inherited structures was considered. Computed post LGM throw-rates confirmed the GPS-determined high deformation rates. The proposed seismogenic source accounts for the high seismic potential of the sector.